2001
DOI: 10.1108/01439910110365430
|View full text |Cite
|
Sign up to set email alerts
|

A compliance device for flexible close tolerance assembly

Abstract: A compliance device combining passive and active compliance has been tested and developed for an anthropomorphic robot for use during assembly operations. The device has the ability to correct for angular and lateral misalignments between mating parts, resulting in no equipment or part damage. The method of control, the design features of the device and the modifications made to enable the device to be used by an anthropomorphic robot are described and future modifications which will enable the device to opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Following this study Edmondson and Redford (2001c) tested and developed a compliance device for an anthropomorphic robot for use during assembly operations based on a gimbal mechanism (see Figure 6). The study concluded that:…”
Section: Manipulator Selectionmentioning
confidence: 99%
“…Following this study Edmondson and Redford (2001c) tested and developed a compliance device for an anthropomorphic robot for use during assembly operations based on a gimbal mechanism (see Figure 6). The study concluded that:…”
Section: Manipulator Selectionmentioning
confidence: 99%
“…To ensure the stability of transmission, the assembly clearance of the gear components is minimal. Due to the influence of measurement uncertainty and positioning error of NCL (Edmondson and Redford, 2001), the existing digital docking system cannot be directly used for the docking of large gear components (Wang et al , 1998). If forced docking, it will lead to large assembly stress between gear components, and the equipment’s overall performance and service life will be affected.…”
Section: Introductionmentioning
confidence: 99%